2012
DOI: 10.1080/03601234.2012.668459
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation of glyphosate and aminomethylphosphonic acid in water and sediment of two Canadian prairie wetlands

Abstract: Glyphosate [N-(phosphonomethyl)glycine] is the active ingredient of several herbicide products first registered for use in 1974 under the tradename Roundup. The use of glyphosate-based herbicides has increased dramatically over the last two decades particularly in association with the adoption of glyphosate-tolerant crops. Glyphosate has been detected in a range of surface waters but this is the first study to monitor its fate in prairie wetlands situated in agricultural fields. An ephemeral wetland (E) and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 26 publications
2
33
0
1
Order By: Relevance
“…Therefore, no cosolvent was required, and both stock solutions of glyphosate and AMPA test items were prepared in deionized water (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) …”
Section: Test Substancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, no cosolvent was required, and both stock solutions of glyphosate and AMPA test items were prepared in deionized water (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) …”
Section: Test Substancesmentioning
confidence: 99%
“…The results of environmental fate studies show that glyphosate is stable to photolytic and hydrolytic degradation in sterile water in all environmentally relevant pH ranges. In contrast, glyphosate is degraded by microorganisms in soil, nonsterile water, and water and sediment systems [2,8]. In soil, microflora degrade glyphosate, under both aerobic and anaerobic conditions [2].…”
Section: Introductionmentioning
confidence: 99%
“…The solubility of glyphosate contributes much to its contamination of surface water, but glyphosate and AMPA bound to particles suspended in water is another means of glyphosate and AMPA transport, known as particle-facilitated transport (Rügner et al, 2014;VandeVoort et al, 2013). Degenhardt et al (2012) reported that 67% of added glyphosate was detected in wetland sediment monitoring within 77 days from June to September. Leaching with drainage is another method of glyphosate and AMPA transport that may lead to potential contamination of, and accumulation in, groundwater (Kjaer et al, 2011;Ruiz-Toledo et al, 2014;Ulén et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…An alternate approach to determining fluxes in aquatic environments is following the fate of a particular compound that has either accidently or deliberately been added to a water body (known as 'spiralling experiments' when carried out in flowing systems). Examples of this approach include studies that have observed the fate of glyphosate and its hydrolysis product (aminomethylphosponic acid) experimentally applied to prairie wetlands [138] and changes in organic P speciation with distance from a poultry operation. [87] However, because of the logistics in performing these types of experiments, they are often restricted to small water bodies like drains, creeks and wetlands.…”
Section: Expansion Of the Types Of Ecosystems Studiedmentioning
confidence: 99%